Organizational Trust During the Early Stages of COVID-19 Pandemic in Poland: Research Report - Lech GÓRNIAK; Małgorzata ADAMSKA-CHUDZIŃSKA (Communications of International Proceedings, 2021)
The focus of the research study are the dramatic changes in the functioning of organizations during the early stages of the COVID-19 pandemic in Poland. Its aim was to assess the impact of the pandemic on relations within the organization, in particular on the attitude of employees towards their employers, expressed as their level of trust in the organization. The study was conducted during the lockdown using the CAWI surveying technique. The study group consisted of 246 employees at non-managerial positions in organizations of various sizes, both from the public and private sector. The ANOVA method was employed for statistical analyses. The results obtained show significantly stable levels of trust in the organization, i.e. only small changes in trust were observed within the study group during the initial stages of the pandemic compared to the pre-pandemic period. However, changes were noted when additional variables used to distinguish subgroups, such as sex, age, organization’s ownership model (private versus public) and education, were taken into consideration. Firstly, improved levels of organizational trust were observed among females employed in the public sector, while the opposite trend was recorded in the private sector for the subgroup. Secondly, organizational trust increased among males without higher education, while male university graduates showed no such change. The results may be useful in predicting organizational behavior, viewed as a crucial component of management, in times of external crises.
Keywords: COVID-19 pandemic; organizational trust; organizational behavior